2017
DOI: 10.1210/jc.2016-3722
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Controlled Trial of a MUFA or Fiber-Rich Diet on Hepatic Fat in Prediabetes

Abstract: Twelve weeks of a MUFA diet decreases hepatic fat and improves both hepatic and total insulin sensitivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
57
2
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(64 citation statements)
references
References 35 publications
2
57
2
2
Order By: Relevance
“…In a randomized, double‐blind clinical trial, the consumption of 20 g/d of olive oil attenuated the fatty liver grade in NAFLD patients . Finally, a randomized trial in prediabetic patients with an isocaloric diet rich in EVOO, reported a decrease in liver fat and an improvement in both hepatic and total insulin sensitivity …”
Section: From Major Foods Groups To Dietary Patterns: Evidence From Nmentioning
confidence: 98%
See 1 more Smart Citation
“…In a randomized, double‐blind clinical trial, the consumption of 20 g/d of olive oil attenuated the fatty liver grade in NAFLD patients . Finally, a randomized trial in prediabetic patients with an isocaloric diet rich in EVOO, reported a decrease in liver fat and an improvement in both hepatic and total insulin sensitivity …”
Section: From Major Foods Groups To Dietary Patterns: Evidence From Nmentioning
confidence: 98%
“…7 Finally, a randomized trial in prediabetic patients with an isocaloric diet rich in EVOO, reported a decrease in liver fat and an improvement in both hepatic and total insulin sensitivity. 23 Because people consume different amounts of various food groups and because of the limited number of large clinical trials, in some cases the impact of different foods are not clear, for example dairy products, coffee and rice. The results of studies on the consumption of dairy products were inconclusive in relation to NAFLD 20 while those on coffee were contradictory (Figure 1).…”
Section: Relationship Between Food Group Intake and Non-alcoholic Fmentioning
confidence: 99%
“…Recent studies have shown large inter-individual variation in response to a meal ( 134 ), which may also explain why individuals respond differently to the same dietary intervention. Indeed, in recent years, several studies have demonstrated that the macronutrient quality and quantity in the diet can lead to a differential response, depending on the individual's metabolic phenotype ( 11 , 12 , 14 , 75 , 135 , 136 ). More specifically, this response may be dependent on liver- or muscle-IR, ectopic fat content, age, ethnicity, sex, and likely other factors that have not been studied extensively thus far.…”
Section: Differential Effect Of Macronutrients On Ectopic Fat In Distmentioning
confidence: 99%
“…Diet and physical activity are key modifiable risk factors that play a significant role in the development, progression and reversal of IR and ectopic fat accumulation ( 5 , 10 ). Related to the diet, not only caloric intake, but also the macronutrient quantity and quality of the diet may affect insulin sensitivity, which may be mediated by changes in ectopic fat accumulation ( 11 14 ). Interestingly, however, recent evidence has shown that the metabolic phenotype of an individual seems to contribute to the inter-individual differences in response to dietary intervention ( 13 , 15 ).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it is characterized by the use of olive oil as the main source of added fat and by a moderate consumption of alcohol during meals (mainly wine). Accordingly, the MedDiet provides plenty of nutrients and bioactive compounds that have been related to the prevention or amelioration of NAFLD, such as PUFAs [ 54 ], MUFAs [ 55 , 56 ], fibre [ 57 , 58 ], low-glycaemic index carbohydrates [ 59 ], vitamins [ 60 , 61 , 62 , 63 ], polyphenols [ 60 , 64 ], terpenes [ 65 , 66 ] and probiotics [ 67 , 68 ]. From a mechanistic point of view and as evidenced both in animal and human studies, the hepatic fat-lowering effects of PUFAs (specially n- 3) could be mainly due to its anti-inflammatory and anti-fibrotic properties, to the up-regulation of hepatic lipolysis and fat oxidation and to the down-regulation of hepatic lipogenesis [ 60 , 69 , 70 ].…”
Section: Meddiet and Fatty Liver Managementmentioning
confidence: 99%